2017
DOI: 10.1186/s12889-017-4809-3
|View full text |Cite
|
Sign up to set email alerts
|

Soil transmitted Helminthiasis and associated risk factors among elementary school children in ambo town, western Ethiopia

Abstract: BackgroundSoil-transmitted helminths (STHs) are widespread in underdeveloped countries. In Ethiopia, the prevalence and distribution of helminth infection varies by different exposing risk factors. We therefore investigated the prevalence of and risk factors of STHs infection in school children living in Ambo town, west Shoa Ethiopia.MethodsIn 2014/15, among 375 school children planed to be included in this study, only 321 school children were recruited in the study. Data onto school children from different sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

18
20
9
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 23 publications
18
20
9
5
Order By: Relevance
“…This study revealed the increased likelihood of children with untrimmed finger nails to be infected with IPIs. This finding is supported by studies conducted on school aged children in Ambo and Butajira towns [23,24]. The explanation would be possible presence of disease causing parasites underneath the nails with dirt [25].…”
Section: Discussionsupporting
confidence: 57%
“…This study revealed the increased likelihood of children with untrimmed finger nails to be infected with IPIs. This finding is supported by studies conducted on school aged children in Ambo and Butajira towns [23,24]. The explanation would be possible presence of disease causing parasites underneath the nails with dirt [25].…”
Section: Discussionsupporting
confidence: 57%
“…in Hintallo-Wejerat (Ethiopia) and 36.5% Kathmandu valley (Nepal) reports were found to be almost in agreement with the current study (Table 4). However, the current study result has been found much higher (4.5 22.8%) than a report from Gondar [5] and Ambo [12] towns in Ethiopia and elsewhere in the world including Taiwan [23], Kenya [17], China [24] and Marshall Islands [25] (Table 4). Still, the present study prevalence was identified lower than study result from Tilili town (44.2%), Wolaita zone (72.2%), Azezo town (72.9%) and Chencha town (81.0%) in Ethiopia (Table 4).…”
Section: Discussioncontrasting
confidence: 85%
“…Poverty, inadequate water supply, sanitation and poor personal hygiene (especially shoe wearing and hand washing) were also previously reported important epidemiological factor for STHs [1,4]. Although several studies have been conducted on the distribution and prevalence of gastrointestinal parasites in Ethiopia [5,[8][9][10][11][12][13], there are still several localities for which epidemiological information is not yet available [14]. This study was aimed to assess the prevalence and risk factors of GIH infection among primary school children of Dembi district, southwest Ethiopia, where data is limited about helminthes infection.…”
mentioning
confidence: 99%
“…Another study in Chencha, Southern Ethiopia also found that overcrowding to be a contributor to helminth infection in school-aged children [22]. Other studies also found that when the family number increases, the occurrence of STH also increases [23,24]. In an overcrowded place, it is hard to keep cleanliness and prevent faecal contamination and pollution of premises hence the risk is high.…”
Section: Discussionmentioning
confidence: 99%